Return to work after sick leave due to musculoskeletal disorder or injury: a longitudinal study conducted in Brazil - João Silvestre Silva-Junior; Maria Carmen Martinez; Felipe Seiti Sekiya; Cristiano Barreto de Miranda; Frida Marina Fischer (BMC, 2023)
Abstract Background Musculoskeletal disorders and injuries (MSDI) are conditions that affect the locomotor system characterized by pain and impairment of functionality. They are the leading cause of years lived with disability. The aim of this study was to analyze the factors that influence the return to work (RTW) among workers on sick leave due to MSDI.   Methods A longitudinal study was conducted in the city of São Paulo, Brazil, between 2020-2022. The participants were 216 workers who required social security compensation due to MSDI. They filled out online questionnaires about their sociodemographic characteristics, health risk behaviors, work characteristics and health conditions. They were followed for 365 days after their first day of sick leave. A Cox regression was performed to identify the factors that influenced their first RTW. Results Most participants were male (53.0%), mean age was 39.5 years (SD 10.6), 70.4% returned to work within the one-year follow-up period. The mean duration of sick leave was 192.6 days. Factors associated with a lower RTW were age 40 years and older (HR 0.54; 95%CI 0.39-0.76) and the interaction between perceptions of the need for improvement in the physical and psychological domains of quality of life (HR 0.67; 95%CI 0.48-0.94). Conclusions Occupational healthcare professionals should pay greater attention to patients who are aging and those with perceived worse physical and psychological conditions, in order to facilitate the reintegration process and promote sustained RTW after sick leave due to musculoskeletal disorder or injury.